2015
DOI: 10.1007/s12229-015-9156-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Plasma Membrane in Saline Conditions: Lipids and Proteins

Abstract: The PM is believed to be one facet of the cellular mechanisms involved in adaptation to saline conditions. Alterations in the PM components in response to salinity are therefore anticipated to contribute to plant salt tolerance. The review provides a comprehensive overview of the recent findings describing the crucial roles of the PM components in plant acclimation to salt stress. The responses of the PM proteins and lipids to salinity in contrasting species/cultivars were therefore discussed. The relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 177 publications
(312 reference statements)
3
43
0
Order By: Relevance
“…Our results in the present study show that all four barley varieties increased the levels of linolenic acid (18:3)containing diacyl-GP species, thereby increasing membrane fluidity in response to salinity. These results are in accordance with previous studies that show that the ability to maintain or increase unsaturated lipids correlates with a high level of salinity tolerance (Lin and Wu, 1996;López-Pérez et al, 2009;Mansour et al, 2015). The increase of linolenic acid in plasma membranes was also reported under salt stress in roots of other barley varieties (Yu et al, 1999;Natera et al, 2016).…”
Section: Both Unsaturation Degree and Carbon Length Distribution Of Gsupporting
confidence: 92%
“…Our results in the present study show that all four barley varieties increased the levels of linolenic acid (18:3)containing diacyl-GP species, thereby increasing membrane fluidity in response to salinity. These results are in accordance with previous studies that show that the ability to maintain or increase unsaturated lipids correlates with a high level of salinity tolerance (Lin and Wu, 1996;López-Pérez et al, 2009;Mansour et al, 2015). The increase of linolenic acid in plasma membranes was also reported under salt stress in roots of other barley varieties (Yu et al, 1999;Natera et al, 2016).…”
Section: Both Unsaturation Degree and Carbon Length Distribution Of Gsupporting
confidence: 92%
“…This again is related to the ability of EB to stabilize the PM under salinity stress and thus may confer salt tolerance (Ding et al, 2012). What supports our contention is the notion that PM is thought to be the primary site of salt injury and hence maintaining its integrity will enhance plant performance in saline conditions (Leopold and Willing, 1984;Cramer et al, 1985;Mansour, 1997Mansour, , 2013Mansour and Salama, 2004;Mansour et al, 2015).…”
Section: Results and Discussion:-supporting
confidence: 76%
“…Perturbation of the PM and hence increased its permeability in response to high salinity has been documented in several previous reports, and was attributed to oxidative stress and ionic impact rather than osmotic stress of salinity (Leopold and . It can be, therefore, inferred that NaCl-induced permeability changes reported here brought about by alterations in the composition of PM lipids and proteins (Mansour et al, 2015). Lipid peroxidation and oxidative damage of proteins of PM may also participate in increased PM permeability induced by NaCl (Mansour, 2013).…”
Section: Results and Discussion:-mentioning
confidence: 69%
“…Several studies demonstrated that salinity affects lipid quality and quantity in glycophyte as well as in halophile plants [25][26][27]; this phenomenon was attributed to the fact that lipids are involved in responses to osmotic stress via their role in maintaining membrane, integrity and fluidity [28].…”
Section: Plantsmentioning
confidence: 99%